The application of UWB1 nuclear fuel depletion code on a CANDU fuel bundle. (July 2016) - Lovecký, M.; Škoda, R.; Hussein, M.S.; Song, J.J.; Chan, P.K.
Abstract: A computer code (UW B1 ) that is applicable for both light and heavy water reactor fuel types is being developed at the University of West Bohemia. CANDU fuel geometry was investigated in this paper. Fuel depletion with UW B1 code was performed and compared to other depletion codes. A feasibility study on the use of burnable absorbers in CANDU to improve operating margins was recently published [1]. The use of slight enriched fuel (SEU) with various burnable absorbers in CANDU has also been considered for future fuel designs. UW B1 is a fast-calculating depletion code. It is being tested and compared extensively to other six different calculation codes, which include both deterministic and probabilistic types. Although the work focuses primarily on the progress of the multiplication factor during fuel depletion, fuel inventory details were also considered. Effective cross sections as the derivation of reaction rates that directly influence Bateman burnup equations were also compared. Further improvement on the UW B1 code is ongoing. The results showed that UW B1 nuclear fuel depletion code is capable to calculate fuel depletion of CANDU fuel bundle with and without burnable absorbers. As expected, the accuracy of the UW B1 code is lower than the other codes. This paper recommends that UW B1 code be considered as a tool for supporting fuel design assessment, since discrepancies are comparable and the code is one to two orders of magnitude faster than other depletion codes. Highlights: The UW B1 code was used to calculate fuel depletion of CANDU fuel bundle. The UW B1 code is one to two orders of magnitude faster than other depletion codes. The advantage offers by the code is its speed that would allow its utilization for various parametric studies.